Evaluating the Use of Lexical Cohesion in Arabic Textbook Published by Indonesian Ministry of Religious Affairs - Reflinaldi Reflinaldi; Awliya Rahmi; Melisa Rezi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
This study evaluates the use of lexical cohesion in Arabic textbooks published by the Indonesian Ministry of Religious Affairs. This qualitative research applies systemic functional linguistics analysis to the Class XII Madrasah Aliyah Arabic textbook. Research data was taken from five reading materials using proficient free-involved listening techniques and analyzed using the framework of lexical cohesion theory. The research results show the use of lexical cohesion devices consisting of repetition (71.4%), synonymy (9.8%), antonymy (3.2%), hyponymy (8.1%), meronymy (6.5%), and collocation (1.0%). From the distribution and quality aspect, lexical cohesion could be more effective and efficient. Quantitatively, the large number of gaps in the lexical cohesion devices shows the ineffectiveness of using cohesion devices. Qualitatively, the uneven distribution of each cohesion device uncovers the ineffectiveness of all reading materials. This study recommends developing reading material in textbooks by using lexical cohesion evenly. Through this development, textbooks will become effective learning instruments to improve students' vocabulary, reading, and writing